Household labour allocation on small dairy farms in eastern Java, Indonesia : implications for gender roles : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Rural Development at Massey University - Utami, Hari Dwi (Massey University, 1999)
The study was carried out in Andonosari village, East Java, Indonesia to investigate the household labour pattern of small-scale dairy farmers. The objectives were to: (a) investigate the pattern of the household labour allocation; (b) examine the earning contribution of dairy fanning to the total of household income; and (c) quantify the role of gender in dairy farming activities. Time use patterns for household labour were computed as the time spent on work (dairy farming and non-dairy farming, including on- and off-farm activities). Interviews were conducted separately with the husband, wife, and family members aged 15-64 years for 50 households. Households were classified into three strata based on the number of dairy cattle farmed: strata 1 (with fewer than 3 animal units (AUs)), n=16; strata 2 (with 3 to 5 AUs, n=18); and strata 3 (with more than 5 AUs, n=16). Descriptive, univariate, bivariate and multivariate analyses were performed using SAS package. Results showed that household labour for income generating activities was allocated more to dairy farming compared to the farm and non-farm work. Females allocated one third of total time to income generating activities, with most of the time devoted to dairy farming activities, while males tended to allocate more time to non-dairy farming activities. The household labour requirement in dairy farming per animal unit decreased as herd size increased, thereby allowing more time for non-dairy activities. Female participation was most evident in feed preparation and feeding, whereas the predominant male activity was forage collection for the dairy cattle. The size of the landholding had no impact on household labour allocation to dairy farming activities. An increase in household income and dependency ratio had a minor impact on household labour requirement in dairy farming. Non-dairy farming activities contributed about two-thirds to household income, the majority from apple farming. The income of household labour per animal unit tended to decrease with an increase in herd size. Variable costs accounted for 74% of the total expenditure in dairy farming, with majority purchases being concentrates. Fixed costs were 26% of total costs, and the major item was depreciation (8%). It is suggested that farmers, including both men and women, should be trained to be more efficient in allocating household labour to dairy farming activities, and in managing the feeding of dairy cattle to achieve high productivity and income. There is substantial scope to increase herd size and increase labour efficiency in dairy farming. Key words : Household labour, gender, dairy farming, non-dairy farming. Title : "Household Labour Allocation on Small dairy Farms in Eastern Java, Indonesia: Implication for Gender Roles." Author : Hari Dwi Utami Degree : Master of Applied Science (Rural Development)
Keywords: Indonesia; Java; Dairy farms; Economic aspects; Home economics; Sexual division of labor